A Short Ride in the Long Walk or the Ponies Posed! - Heath, William, 1795-1840 - also known as Paul Pry (Fores, S. W., 1824)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Carriages & coaches; Great Britain -- Social life and customs -- 19th century -- Caricatures and cartoons